Optimum design and performance analysis of a gas lift system in the carbonate reservoir of Ahdab oil field - Alsrray, Hayder H.; Farman, Ghanim M. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Gas lift is one of the most important artificial lift methods for increasing oil production, as wells often require this method after the reservoir's energy has decreased. In this research, an optimal gas lift system is designed for five horizontal wells in the Ahdab oil field, which suffers from low production. At the same time, water cut in some of these wells reaches 66%, while the productivity index is low in others, which makes the challenges clear, and a deep analysis is needed to find an optimal system. The Pipesim program is used to design the optimal gas lift system, which contains features that facilitate the implementation of the appropriate design and provide the ability to analyze and determine the optimal design values, as well as to detect future production problems. A single system is designed for wells located in the same formation, where an injection pressure of 1750 psi, an injection rate of 1 mmscf/d, and a wellhead pressure of 300 psi are chosen for wells in the Mishrif formation, noting that three valves will be installed in the system. For the wells in the Rumaila formation, an injection pressure of 1950 psi, an injection rate of 1.25 mmscf/d, a wellhead pressure of 475 psi, and four valves were selected for the unloading process. The results proved the design efficiency and that the selected values ​​were optimal, as the increase in production for the five wells was 238%, 146%, 56.6%, 55.9%, and 37.4%.